Sporting activity is reduced following medial reefing performed for patellar dislocation - C. Ihle; J. Maurer; P. Ziegler; U. Stöckle; A. Ateschrang; M.-D. Ahrend; S. Schröter (BMC Musculoskeletal Disorders, 2019)
Abstract Background Patellar dislocation is common in young and active patients. The purpose of this study was to determine sporting activity following the medial reefing of patellar dislocation. Methods One hundred forty-four patients with objective patellar dislocation were treated between 2004 and 2013. Three groups were analyzed retrospectively with a minimum follow-up of 24 months: (1) primary dislocation that was treated with medial reefing without a recurrent dislocation until the day of follow-up (n = 74), (2) primary dislocation that was initially treated with medial reefing but with a recurrent dislocation until the day of follow-up (n = 44), and (3) medial reefing after failed conservative treatment (n = 26). Sporting activity was assessed using a widely-used sporting activity questionnaire and the Tegner score prior to the injury and at the follow-up (58.7 ± 22.6 months after the injury). Clinical outcomes were assessed using IKDC and Kujala score. Results The Kujala score was 94.7 ± 9.3 for Group 1, 84.1 ± 16.6 for Group 2 and 93.4 ± 9.7 for Group 3. IKDC at the time of follow-up was 97.2 ± 9.3 for Group 1, 86.1 ± 14.6 for Group 2 and 95.1 ± 11.1 for Group 3. 91.9% of Group 1 and 92.3% of Group 3 were active in sports prior to their injuries and at the time of the follow-up. In Group 2, sporting activity reduced from 81.8 to 75.0%. In all groups, a shift from high performance to recreational sports was found. Conclusions Despite good clinical results, sporting activity was reduced following patellar dislocation treated with medial reefing. Also, a shift from engagement in high- to low-impact sports among the participants was noted.